Phenolic compounds of mango (Mangifera indica) by-products: Antioxidant and antimicrobial potential, use in disease prevention and food industry, methods of extraction and microencapsulation - Tirado-Kulieva, Vicente (2021)
Globally, a large amount of agri-food waste is generated as a result of industrial processes or direct consumption of raw materials, and when discarded, they represent a factor of environmental pollution. Mango by-products have a great bioactive potential, especially because they contain phenolic compounds in which mangiferin predominates, in addition to a great variety of phenolic acids, flavonoids and tannins, which confer antioxidant effects against cancer, cardiovascular and neurological diseases, among others. In addition, it was demonstrated that they have an effect against a broad microbial spectrum, including multiple pathogenic bacteria and fungi such as Escherichia coli and Candida albicans, respectively. According to the literature, mango peel and seed extracts also have potential as an additive, by influencing the sensory and physicochemical characteristics of foods, which has been proven by their addition to products such as shrimp, yogurt and cookies. Considering the importance of mango by-products, this work focused on their phenolic properties, the mechanism of antioxidant and antimicrobial action, their fields of pharmacological and food applications, in addition to evaluating their extraction methods and proposing microencapsulation as a suitable technology to avoid their degradation and control their release under appropriate conditions. Based on the analysis performed, further studies are suggested on the application in different foods and to evaluate the interaction of polyphenols with the compounds of the product, to avoid possible negative effects. It is also recommended to experiment with the use of combined technologies to improve results during extraction and microencapsulation.